Cosatu’s mute response: Waves of social movement unionism in South Africa and its crisis during Covid - Nkosi, Mbuso (New Agenda: SA Journal of Social and Economic Policy, 2024)
Cosatu’s failure to be the voice of the working class in times of crisis, such as during Covid-19 and the July 2021 unrest in KwaZulu-Natal and Gauteng, reflects its inability to envision a future beyond the ANC, writes uMBUSO weNKOSI. He argues that as long as organised labour is locked in an alliance with the ruling party it cannot be rooted in community struggles, to the detriment of the social movement unionism of the anti-apartheid struggle.